Comparison of Nicotine Pharmacokinetics in Healthy Japanese Male Smokers Following Application of the Transdermal Nicotine Patch and Cigarette Smoking - Sobue, Satoshi; Irie, Shin; Akasaki, Moriaki; Kikkawa, Hironori; Sekiguchi, Kaneo (Biological & Pharmaceutical Bulletin, 2006)
Transdermal nicotine patch (TNP) contains approximately 16.6 and 24.9 mg of nicotine per 20 and 30 cm2 (TNP-20 and TNP-30). The aims of the study are to investigate linearity of nicotine pharmacokinetics after single application of different strengths of TNP and to directly compare plasma nicotine concentrations with those during cigarette smoking. Twelve healthy Japanese male smokers were randomly allocated to 1 of 2 cohorts consisting of 6 subjects each. Cohort 1 subjects received 1 sheet of TNP-20 (TNP-20×1) in period 1, and 2 sheets of TNP-20 (TNP-20×2) in period 3. Cohort 2 subjects were received 1 sheet of TNP-30 (TNP-30×1) in period 2, and smoked a total of 12 cigarettes at 1 h intervals in period 4. Each TNP was applied to the upper arm for 16 h. After TNP-20×1 or TNP-20×2 treatment in cohort 1, the amount of nicotine delivered from TNP (Dose) was proportional to surface area of TNP. Cmax and AUC of nicotine increased with the surface area (Dose), and tmax, t1/2, CL/F and percentage of dose excreted in urine were almost the same between both treatments. These suggest the linear pharmacokinetics of nicotine in proportion to the surface area and Dose following single application of TNP in identical subjects. In cohort 2, the plasma nicotine concentrations after TNP-30×1 treatment were approximately half those just before each smoking.